TAFSIR NORMATIF TERHADAP PERKEMBANGAN POLITIK HUKUM EKONOMI SYARIAH - Solihin, Dadin (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2021)
The development of sharia law and economy is in line with Indonesia's national development goal of achieving the creation of a just and prosperous society based on economic democracy. Then developed an economic system based on the value of justice, togetherness, equality, and benefits by sharia principles. The politics of national law, placing a strong side on the legislation of Islamic law, both on the institutional aspect, and the substance of its arrangements. This makes it clear that the existence ofMuslims as the majority of Indonesians is given good legal protection by the state, especially in conducting sharia financial transactions. This is seen, substantially the existence of Islamic law, especially the muamalah law has been made part of the national positive law in Indonesia. Legal research methodology with a descriptive method that is a method that describes a data condition as it is, where there is no intervention of the author in the form of reduction or addition of data, but no interpretation, with the method of approach normatively that is the approach of literacy studies accompanied by the study of legislation related to financing agreements in LKS, by using and paying attention to empirical data as a supporting factorthat is presented in a normative juridical manner. Keywords: Politics, Law, Sharia Economy.